Regional point prevalence study of healthcare-associated infections and antimicrobial use in acute care hospitals in Liguria, Italy. Issue 1 (May 2018) - ,; Alicino, C.; Barberis, I.; Faccio, V.; Grammatico, F.; Magnasco, L.; Paganino, C.; Saffioti, C.; Sarteschi, G.; Ungaro, R.; Bellina, D.; Daturi, V.; et al.
Summary: Background: Given the importance of monitoring healthcare-associated infections (HCAIs) and the consumption of antibiotics, a regional point prevalence survey was conducted in Liguria between March and April 2016. Aim: To measure the overall prevalence of HCAI and describe the use of antibiotics in all public hospitals. Methods: Data on risk factors and use of antibiotics were collected for each hospitalized patient. To define the variables significantly associated with HCAI, univariate and multivariate analyses were conducted. Standardized infection ratio and standardized antimicrobial use ratio were measured for each participating hospital. Findings: A total of 3647 patients were enrolled. In all, 429 HCAIs were diagnosed in 376 patients, giving a prevalence of HCAI of 10.3%. Respiratory tract (21.7%) and urinary tract (20%) were the most frequent sites of infection. High rates of meticillin-resistant Staphylococcus aureus (47.4%) and Enterobacteriaceae resistant to carbapenems (26.3%) were isolated. Forty-six percent of patients received at least one antibiotic. Combinations of penicillins including β-lactamase inhibitors (24.1%) were the most widely used; the main indication (46.7%) was the treatment of a community-acquired infection. Conclusion: There was an increase in HCAI prevalence compared to a similar survey conducted in 2007; however, the performance of overlapping investigations will enable more reliable considerations. Nevertheless, data on antimicrobial resistance and use of antibiotics are consistent with the national trend. Despite methodological limitations, prevalence studies are useful to monitor HCAI over time and encourage greater awareness of the problem by all stakeholders.